Edukasi Gizi Ibu dan Pemberian Makanan Tambahan terhadap Pengetahuan, Praktik Ibu dan Pertumbuhan Anak: Studi Kuasi-Eksperimental di Kupang: Edukasi Gizi Ibu dan Pemberian Makanan Tambahan terhadap Pengetahuan, Praktik Ibu dan Pertumbuhan Anak: Studi Kuasi-Eksperimental di Kupang - Nur, Astuti; Louisa Sine, Juni Gressilda; Sanjiwani, Putu Amrytha; Costa, Santa Luciana Diaz Vera Da; Loaloka, Meirina Sulastri (Universitas Airlangga, 2026)
Background: Stunting remains a major nutritional problem in Indonesia, particularly in East Nusa Tenggara (NTT), with a prevalence of 37.9% in 2023. Nutritional deficiencies in the first 1000 days of life affect children's physical growth, cognitive development, and productivity. Causative factors include exclusive breastfeeding practices, complementary feeding, daily protein intake, immunization, infectious diseases, and household economic and environmental conditions. Maternal education is considered important for improving knowledge and practices of good feeding.Objective: To determine the effectiveness of nutrition education interventions for mothers and the provision of supplementary feeding on mothers' knowledge and practices, as well as the growth of children under five in Kupang City, East Nusa Tenggara. Methods: A quasi-experimental study with a pre-test post-test control design, involving 60 toddlers (30 intervention, 30 control). Interventions include maternal nutrition education (CGM, CDM, IYCF) and protein supplementation (eggs). The data includes maternal knowledge and practices, as well as child anthropometry. The analysis used t-tests and chi-square tests (p<0.05).Results: The intervention significantly improved mothers' knowledge, as evidenced by an increase in scores on CGM by 11.37, CDM by 13.13, and IYCF by 13.93. There was also an improvement in parenting practices, particularly in CGM (36.67) and CDM (25.67), while the improvement in IYCF practices was relatively slower and only reached significance at the second follow-up. For child anthropometry, the changes were limited, with a significant increase in height in post-test 1 of 0.49 cm, while the weight changes did not reach significance. Conclusion: Interactive nutrition education is effective in improving mothers' knowledge and practices, but its impact on child growth requires long-term intervention, environmental support, and sustainable nutritional fulfillment